The Multifaceted Effects of Serotonin Transporter Polymorphism (5-HTTLPR) on Anxiety, Implicit Moral Attitudes, and Harmful Behaviors - Martínez, Róger Marcelo; Chen, Chin-Yau; Liao, Tsai-Tsen; Cheng, Yawei; Fan, Yang-Teng; Chou, Shih-Han; Chen, Chenyi (Frontiers in Psychology, 2020)
Morality is fundamentally human in nature. Regardless, and even when moral norms seem to work towards the common goal of human cooperation, which morally contentious behaviors are permitted and which are prohibited vary across populations. Due to this occurrence, much scientific debate has revolved around the notion that this phenomenon might be explained by the interaction between genes and environment. Alongside, whether the principles cementing the bases of morality are intuition- or reason-based is another question that has been raised. However, previous research addressing these topics used explicit measures to probe moral attitudes, thus, being the participants able to intentionally modify or disguise their honest responses. What’s more, while the 5-HTT gene was found to be associated with anxiety, morality, and even cultural structures, a single genotype-phenotype linkage cannot be established without considering the multifaceted effects of the 5-HTT gene on gene-behavior interactions. In order to explore the role of genetics on modeling moral attitudes and behaviors, we genotyped the 5-HTTLPR in 114 healthy volunteers, and subsequently assessed their explicit justice sensitivity (JSI) and moral permissibility judgments, as well as their implicit moral attitudes (mIAT). Results revealed that 5-HTTLPR short-allele carriers had significantly lower mIAT reaction times when answering correctly, and were less compliant on harming another person even when harm or death would inevitably occur anyway to this other individual. With these preliminary results, we can first see how it doesn’t have to be a matter of vouching for a rationalist versus an intuitionist model of moral judgment, but rather being moral judgment an outcome of the different variants of the 5-HTTLPR polymorphism affecting the way in which individuals engage contrastingly with moral issues.